THEMATIC EXPLORATION OF PRAGMATICS, SPEECH ACT THEORY AND DISCOURSE ANALYSIS IN LINGUISTIC COMMUNICATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of three key concepts in linguistics: pragmatics, speech act theory, and discourse analysis. It outlines the core principles and distinctions within each framework, emphasizing their relevance to understanding how language functions beyond its literal meaning. Pragmatics is presented as the study of language in context, focusing on how meaning is influenced by factors like implicature, deixis, and speaker intent. Speech act theory is examined in terms of its categorization of language into locutionary, illocutionary, and perlocutionary acts, highlighting how language is used to perform actions. Discourse analysis is explored as the study of larger communicative units, such as conversations and texts, and its role in understanding coherence, power dynamics, and social structures. The article concludes by demonstrating how these theories are interrelated and applicable across various fields, from education to artificial intelligence, showcasing the broader implications for social interaction and communication. This annotation captures the central themes and applications discussed in the article, providing a concise summary for those interested in understanding the complexities of human communication and the tools used to study it.